A Newly Observed Deep Countercurrent in the Subtropical Northwest Pacific. Issue 7 (8th July 2021) - Azminuddin, F.; Jeon, D.; Kim, Y. H.; Jang, C. J.; Park, J.‐H.
Abstract: The existence of a deep countercurrent in the subtropical northwest Pacific, named Subtropical Deep Countercurrent (STDCC), has been revealed by moored current‐meter data obtained from a buoy system (∼21.6°N, ∼132.8°E) during 4 years (2010–2014). The climatological average of Argo‐based absolute geostrophic velocities and ocean reanalyzes have further confirmed the spatial picture of the eastward‐flowing STDCC. STDCC is identified as a time‐mean feature in the latitudinal range of 19°–25°N with a meridional scale of 200–300 km that persistently appears from 125° to 180°E and slightly shifts to the north as it goes east. Vertically, STDCC is mostly found below 1, 000 m with its core located between the depths of 1, 250 and 2, 000 m, which corresponds to the undercurrent's meridional pattern with increasing depth northward and a meridional space of 2°–4°. Nevertheless, STDCC is distinctive where it lies along ∼27.6 −  σ θ, which is deeper than the North Equatorial Undercurrent's density layer (∼27.0 −  σ θ ). The mean velocity of STDCC at 2, 000 m observed by mooring measurements was approximately 0.2 ± 0.15 cm s −1 with a maximum speed of approximately 5.59 cm s −1 . The ocean reanalyzes also support the existence of STDCC with mean velocity of approximately 0.2–0.6 cm s −1 west of 145°E and can be as large as 1.6 cm s −1 at the eastern region. The results show that STDCC is closely related to the westward‐propagating eddies. Our finding emphasizes that the convergence of the cyclonic and anticyclonic eddies possibly generates time‐mean zonally elongated eastward flows forming STDCC feature. Plain Language Summary: Information about the deep circulation in the subtropical northwest Pacific is very limited owing to a lack of observational evidence. By using direct current measurements for 4 years (2010–2014), this study provides a description of the first observation of the newly identified deep eastward flows, named Subtropical Deep Countercurrent (STDCC). Argo‐based absolute geostrophic currents and ocean reanalyzes have further confirmed the existence of this current, which found around 19°–25°N at 125°–180°E longitude and core's depths of between 1, 250 and 2, 000 m. The maximum mean velocity of STDCC at 2, 000 m observed by mooring measurements was approximately 0.2 ± 0.15 cm s −1 with a maximum speed of approximately 5.59 cm s −1, which is relatively weaker than the tropical North Equatorial Undercurrent (NEUC) and the upper‐layer Subtropical Countercurrent. In comparison, the model results show that STDCC has typical velocity of approximately 0.2–0.6 cm s −1 west of 145°E and greater velocity at the eastern region reaches 1.6 cm s −1 . The westward‐propagating eddies have been suggested as being the possible dynamics behind the STDCC's generation. Key Points: A newly identified deep countercurrent has been found in the subtropical northwest Pacific from observations and ocean reanalyzes Subtropical Deep Countercurrent (STDCC) is identified in the range of 19°N–25°N, and 125°E to 180°E with its core depths between 1, 250 and 2, 000 m The generation of STDCC is strongly associated with the westward‐propagating eddies